PROYEK PENINGKATAN JALAN BUBE-BULOTALANGI BONE BOLANGO - Bumulo, Ronny; Latinulu, Atrila (Universitas Bina Taruna Gorontalo, 2024)
The Bube - Bulotalangi road improvement project aims to improve the function of the road so that the road returns to its own function. In Tamboo village itself, a road improvement project was carried out on the access road to Center Point and Campus 4 of Gorontalo State University. This service aims to facilitate road access for students who want to go to campus 4 of Gorontalo State University and people who want to visit Center Point. The Bube - Bulotalangi Road Improvement Project is work carried out in Bone Bolango Regency with a length of 2130 meters.